Effect of Gibberellic Acid and Waxing on Quality and Storability of Lime Fruits (University of Khartoum Journal of Agricultural Sciences, 2023)
The effect of post-harvest treatment of gibberellic acid (GA3 )and/or waxing on quality and storability of lime fruits at 18 ± 1oC and85% – 90% relative humidity was evaluated. Treatment with 50 and 100ppm GA3 delayed senescence, maintained quality and extended storagelife of lime fruits. The higher the concentration of GA3 the more was theeffect. Treatment with GA3 and waxing was more effective than treatmentwith GA3 alone. The effects of GA3 and/or waxing in delayingsenescence, maintaining quality and extending storage life of limes wasmanifested in reduced respiration rate, weight loss, fruit softening andtotal soluble solids accumulation, delayed peel colour development(degreening), decreased titratable acidity and increased ascorbic acidretention.
Keywords: Lime fruits; gibberellic acid; fruit quality; storability